Enhancing Lecturer Performance Through Readiness to Change: The Influence of Transformational Leadership and Organizational Culture - Nurjannah; Rojuaniah; Abdul Haeba Ramli; Lia Amalia; Lukman Cahyadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study examines how transformational leadership and organizational culture play a role in shaping the readiness of Generation X lecturers at private universities to face change, as well as its impact on lecturer performance. This study was conducted using a quantitative approach through the distribution of questionnaires to 175 lecturers in Jakarta and analyzed using the SEM-PLS method. This study aims to answer how these two independent variables influence readiness to change and lecturer performance, both directly and indirectly. The results show that organizational culture and transformational leadership have a positive influence on readiness to change, while readiness to change acts as a significant mediator in the relationship between these variables and lecturer performance. However, the direct influence of transformational leadership on lecturer performance is not significant. This article discusses the importance of readiness to change as a psychological variable that bridges the dynamics of leadership and organizational culture with performance outcomes. These findings contribute conceptually to change management studies and provide practical implications for higher education institutions in enhancing lecturer readiness and performance in the face of organizational dynamics.